Microbial Biocapsules as Generally Recognized-As-Safe Fungal-Based Immobilized Cell Technology for Precision Sequential Fermentations of Grape Must - Juan Carbonero-Pacheco; Florina Constanta-Mustafa; Raquel Muñoz-Castells; Juan Carlos Mauricio; Juan Moreno; Teresa García-Martínez; Jaime Moreno-García (Fermentation)
This work focuses on the production of a white wine with a specific organoleptic profile by means of sequential fermentation using immobilized yeast in a system known as “microbial biocapsules”. Three fermentation conditions were created: sequential fermentation with immobilized yeast (SqFMB) employing a matrix composed by Aspergillus oryzae (pellet-forming fungus recognized as GRAS), sequential fermentations with non-immobilized yeast cells (SqF), and a control of spontaneous fermentation (SpF). To carry out these fermentations, Pedro Ximénez grape must was used and two non-Saccharomyces yeast strains, Debaryomyces hansenii LR1 and Metschnikowia pulcherimma Primaflora, and the Saccharomyces cerevisiae X5 strain were used. The wines produced were subjected to microbiological and chemical analyses in which metabolites that positively influence the wine profile, such as 1,1-diethoxyethane and decanal, are only produced in the SqFMB condition, and others, like nonanal, were detected in higher concentrations than in SqF and SpF. Microbiological analyses show that less non-Saccharomyces yeasts were isolated in the SqFMB condition than in SqF, which indicates an efficiency in the inoculation and removal method proposed. These results conclude that microbial biocapsules seem to be a good yeast carrier for wine elaboration; however, modulation of some variables like yeast concentration inocula, the employment of preadaptation methods or the use of yeast species with higher fermentative power need to be tested to improve the novel methodology.